AGE COMPOSITION, DENSITY, NUMBER OF THE ENDEMIC SPECIES ARTEMISIA HEPTAPOTAMICA POLJAK (Experimental biology, 2021)
The article describes Artemisia heptapotamica Poljak, which is found in the northern Tian Shan region. The habitat, age composition, number, density and distribution range of the endemic species are described. The endemic species are the weakest objects. As their habitat is narrow and often does not withstand the impact of anthropogenic factors, the study shows a lack of  vegetative individuals. As a result, the study is prioritized due to the extinction threat. The determination of the number, density, and age composition of coenopopulations was carried out using the methods of A. A. Uranov, O. V. Smirnov, and T. A. Rabotnov. Three main populations were taken for the study - Bartogai reservoir, coenopopulations of The Alatau (population 1), near of Shonji, the Alatau (population 2), villages of Kokpek, the Alatau (population 3).